Acellular therapeutic approach for heart failure: in vitro production of extracellular vesicles from human cardiovascular progenitors. (6th February 2018) - El Harane, Nadia; Kervadec, Anaïs; Bellamy, Valérie; Pidial, Laetitia; Neametalla, Hany J; Perier, Marie-Cécile; Lima Correa, Bruna; Thiébault, Léa; Cagnard, Nicolas; Duché, Angéline; Brunaud, Camille; Lemitre, Mathilde; et al.
Abstract: Aims: We have shown that extracellular vesicles (EVs) secreted by embryonic stem cell-derived cardiovascular progenitor cells (Pg) recapitulate the therapeutic effects of their parent cells in a mouse model of chronic heart failure (CHF). Our objectives are to investigate whether EV released by more readily available cell sources are therapeutic, whether their effectiveness is influenced by the differentiation state of the secreting cell, and through which mechanisms they act. Methods and results: The total EV secreted by human induced pluripotent stem cell-derived cardiovascular progenitors (iPSC-Pg) and human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) were isolated by ultracentrifugation and characterized by Nanoparticle Tracking Analysis, western blot, and cryo-electron microscopy. In vitro bioactivity assays were used to evaluate their cellular effects. Cell and EV microRNA (miRNA) content were assessed by miRNA array. Myocardial infarction was induced in 199 nude mice. Three weeks later, mice with left ventricular ejection fraction (LVEF) ≤ 45% received transcutaneous echo-guided injections of iPSC-CM (1.4 × 10 6, n  = 19), iPSC-Pg (1.4 × 10 6, n  = 17), total EV secreted by 1.4 × 10 6 iPSC-Pg ( n  = 19), or phosphate-buffered saline (control, n  = 17) into the peri-infarct myocardium. Seven weeks later, hearts were evaluated by echocardiography, histology, and gene expression profiling, blinded to treatment group. In vitro, EV were internalized by target cells, increased cell survival, cell proliferation, and endothelial cell migration in a dose-dependent manner and stimulated tube formation. Extracellular vesicles were rich in miRNAs and most of the 16 highly abundant, evolutionarily conserved miRNAs are associated with tissue-repair pathways. In vivo, EV outperformed cell injections, significantly improving cardiac function through decreased left ventricular volumes (left ventricular end systolic volume: −11%, P  < 0.001; left ventricular end diastolic volume: −4%, P  = 0.002), and increased LVEF (+14%, P  < 0.0001) relative to baseline values. Gene profiling revealed that EV-treated hearts were enriched for tissue reparative pathways. Conclusion: Extracellular vesicles secreted by iPSC-Pg are effective in the treatment of CHF, possibly, in part, through their specific miRNA signature and the associated stimulation of distinct cardioprotective pathways. The processing and regulatory advantages of EV could make them effective substitutes for cell transplantation.